2004
DOI: 10.4315/0362-028x-67.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Long-Haul Transport and Lack of Preconditioning Increases Fecal Shedding of Escherichia coli and Escherichia coli O157:H7 by Calves

Abstract: The effects of weaning and transport on fecal shedding of Escherichia coli and on E. coli O157:H7 were investigated using 80 Angus and 94 Charolais range steer calves blocked by breed and assigned to four treatments. The calves were or were not preconditioned before transport on commercial cattle liner to the feedlot via long (15 h) or short (3 h) hauling duration, yielding preconditioned long haul (P-L; n = 44), preconditioned short haul (P-S; n = 44), nonpreconditioned long haul (NP-L; n = 43), and nonprecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…We have previously observed that a rifampinresistant isolate introduced (via oral inoculation) into a subset of cattle in a feedlot pen was acquired and shed in the feces of all animals in the pen within 48 h of introduction (58). Transmission of this isolate between pens of cattle was observed only during the week immediately after the animals' entry to the feedlot, a period in which stress may have altered the stability of microbial populations within the digestive tract (3,9). Coincidently, the increase in shedding on day 113 occurred during the beginning of the transition phase to the grain-based diet, a period of ecological shift in the makeup of the microbial populations within the digestive tract.…”
mentioning
confidence: 99%
“…We have previously observed that a rifampinresistant isolate introduced (via oral inoculation) into a subset of cattle in a feedlot pen was acquired and shed in the feces of all animals in the pen within 48 h of introduction (58). Transmission of this isolate between pens of cattle was observed only during the week immediately after the animals' entry to the feedlot, a period in which stress may have altered the stability of microbial populations within the digestive tract (3,9). Coincidently, the increase in shedding on day 113 occurred during the beginning of the transition phase to the grain-based diet, a period of ecological shift in the makeup of the microbial populations within the digestive tract.…”
mentioning
confidence: 99%
“…Cattle are a major reservoir of E. coli O157:H7 (2, 4, 5, 7), and cattle water troughs are important sources of the pathogen on farms (2,4,5,7,17,20,21,27,28,37). Studies have further revealed that when present in cattle drinking water, the pathogen was disseminated to other cattle consuming the contaminated water (19,29).…”
mentioning
confidence: 99%
“…Esta medida es relevante, ya que los animales durante el transporte podrían incrementar la diseminación de agentes como E coli O157 y Salmonella spp., los cuales tienen la capacidad de sobrevivir por periodos prolongados en este ambiente (Brandt et al 2008;Bach et al 2004). Existe un grado aceptable de la mayoría de las medidas evaluadas, a excepción de la existencia de un proceso de desinfección, sin embargo esta deficiencia se compensa con la existencia de acceso restringido y estacionamientos en la periferia, lo que disminuiría el riesgo de ingreso de agentes patógenos.…”
Section: Ingreso De Vehículosunclassified